Effect of multicomponent fouling during microfiltration of natural surface waters containing nC60 fullerene nanoparticles. Issue 4 (2nd June 2017) - Floris, R.; Moser, G.; Nijmeijer, K.; Cornelissen, E. R.
Abstract : To understand and mitigate the role of surface water composition and associated membrane fouling in the removal of nC60 nanoparticles by low-pressure membranes, experiments were carried out with microfiltration membranes using natural feed waters, mimicking separation in real industrial water treatment plants. Abstract : To understand and mitigate the role of surface water composition and associated membrane fouling in the removal of nC60 nanoparticles by low-pressure membranes, experiments were carried out with microfiltration membranes using natural feed waters, mimicking separation in real industrial water treatment plants. The effects of water composition, the presence of nanoparticles, and membrane fouling were investigated with a dead-end bench-scale system operated under constant flux conditions including a hydraulic backwash cleaning procedure. nC60 nanoparticles can be efficiently removed by microfiltration and the removal efficiency is found to be independent of the water surface composition. However, the water composition controls the extent of fouling occurring during filtration. A synergistic effect on membrane fouling between nC60 and surface water constituents such as natural organic matter (NOM) and its fractions is observed: the synergistic effect resulted in a transmembrane pressure (TMP) increase always higher than the sum of the TMP increase due to the filtration of nC60 in ultrapure water and the TMP increase due to the surface water without nC60 .